PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN KAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Rangkuti, Rara Beby Fahira; Listiorini, Listiorini; Azhar, Karya Satya (Journal Accounting International Mount Hope, 2025)
The purpose of this study was to determine how working capital turnover and cash turnover affect firm value in manufacturing companies listed on the Indonesia Stock Exchange, using profitability as a moderating variable. This type of research is quantitative and associative. The population used in this study are manufacturing companies listed in 2018-2023 on the Indonesia Stock Exchange (IDX). With 58 organizations selected for six years of observation, the sampling technique used purposive sampling, resulting in a total of 206 observations. The findings of this study indicate that the value of a company is not significantly affected by working capital turnover and cash turnover. For manufacturing companies listed on the Indonesia Stock Exchange, profitability can reduce the impact of working capital turnover on firm value between 2018 and 2023.